Przyczyny wypadków drogowych na tle teorii przyczynowości - Dudkowiak, Zbigniew (Wydział Prawa i Administracji UAM, 1973)
The problem of finding out the exact causes of road accidents is one of the most controversial problems being under discussion in the field of road safety. There are no satisfactory definitions of the basic notions relevant to the causes of accidents and the accident itself and it is why investigation of the mechanism of a road accident and its causes is faced with difficulties. This results in an imperfect statistical classification of road accidents, and classification is the basis of research into any quantitative phenomena and a component of the statistical method. The question to be answered is which definition of the cause of a road accident should be accepted as a tool for selecting the causes for statistical purposes. After a rough analysis of practical application of numerous conceptions of causation used in various fields founded on the theory of casual nexus it can be noted that „the theory of equivalent causes" applied by criminal law may also serve to work out methods of preventing accidents. On the grounds of the assumptions of that theory and an analysis of the views up to now of the adaptation of the theory for preventive purposes it seems useful to assume that „equivalent conditions" existing before an accident, which could be eliminated or whose influence could be limited, are the cause of the accident. If in the statistics of road accidents several causes of an accident are given according to the suggested criterion, the field of observation is much larger and the accuracy of selecting causes is increased and consequently the statistical observation for basic research purposes is of greater value.
Causes of Road Accidents against the Background of the Theory of Causation